OCORRÊNCIA DA MOSCA-NEGRA-DOS-CITROS, Aleurocanthus woglumi ASHBY (HEMIPTERA: ALEYRODIDAE) NO ESTADO DE SÃO PAULO - Pena, Márcia Reis; Vendramim, José Djair; Lourenção, André Luiz; Silva, Neliton Marques da; Yamamoto, Pedro Takao; Gonçalves, Maiara da Silva (REVISTA DE AGRICULTURA, 2015)
OCORRÊNCIA DA MOSCA-NEGRA-DOS-CITROS, Aleurocanthus woglumi ASHBY (HEMIPTERA: ALEYRODIDAE) NO ESTADO DE SÃO PAULO